Management of Visual and Interactive Content Development for Banking Services Promotion on Instagram - I Wayan Andra Wirawan; Komang Widhya Sedana Putra P; Ni Wayan Lasmi (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The business sector has been significantly impacted by the swift progress of information and communication technology, which has dramatically altered many facets of human existence. Instagram and other social media platforms have grown to be indispensable resources for businesses looking for creative ways to interact with their clientele. This service was designed to help PT BPR Mas Giri Wangi market their banking services on Instagram by enhancing their visual and interactive content. The main objectives of the campaign were to improve customer relationships, boost interactivity and reach, and produce engaging content. Descriptive qualitative research was used in this project, which was perfect for examining the subtleties of user involvement and content development. The first step of the procedure involved gathering a lot of data via interviews and observation, then evaluating Instagram activity, likes, comments, and content kinds. Deeper insights into current plans and difficulties were obtained through interviews with the marketing staff. After gathering data, the group created a thorough content strategy that included choosing a theme, planning posts in advance, and making use of Instagram's interactive features, such as reels and stories. Creating visually beautiful and captivating content for the bank's target demographic was part of the content production process. In the last stage, Instagram Insights was used to track and assess the results, revealing a notable rise in interaction and content reach. These improvements demonstrated the value of a smart social media approach in today's business environment by helping PT BPR Mas Giri Wangi draw in new potential clients and fortify current ones.